Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Rumah Sakit Khusus Gigi Dan Mulut: Systematic Literature Review - Refliza Yanti; Andi Supriatna (Universitas Muhamadiyah Manado, 2023)
Hospitals as health service providers must know how the quality of service they provide can give satisfaction to patients. Competition between hospitals is getting tougher and sharper so that every hospital is required to enhance its competitiveness by trying to provide satisfaction to all of its patients. Service quality will be considered satisfactory, if the perception exceeds expectations; Service quality will be considered good or adequate if it is in line with expectations, and will be considered bad if the service is bad or not good enough. The purpose of this study was to determine the effect of service quality seen from various dimensions, namely tangibles, responsiveness, reliability, assurance, and empathy on patient satisfaction at the Special Dental and Oral Hospital in Bandung. This literature review uses articles in published Connected Papers in 2017-2022, 108 articles. The results of the 5 articles show that service quality and patient satisfaction are directly proportional, if the service quality is good then customer satisfaction will be good and if the service quality is bad then the level of patient satisfaction is also bad.